Collectivize! : essays on the political economy of urban form - Angélil, Marc. (Essays on the political economy of urban form, 2025)
This second book in the 'Essays on the political economy of urban form' series, developed at ETH Zurich's WERK 11 and edited by Marc Angélil and Rainer Hehl, revisits the idea of the 'common'. By taking the reader on a trip through built social experiments and fictional utopias, this collection of four essays considers the role of collective organization and identity in an increasingly individualized world. Robert Owen's New Harmony, the kibbutz in Israel, and North Korea provide case studies for the book, which are complemented with a theoretical exploration of the practice of 'commoning' and how it relates to the middle class. With contributions by Massimo De Angelis, University of East London; Jesse Le Cavalier, ETH Zurich; Arno Brandlhuber and Christian Posthofen, Akademie der Bildenden Künste Nürnberg; and Zvi Efrat, Bezalel Academy of Arts and Design Jerusalem.